A NEW OBJECTIVE CRITERION FOR IRIS LOCALIZATION - Basit, A. (The Nucleus, 2010)
Iris localization is the most important step in iris recognition systems. For commonly used databases, exact data is not given which describe the true results of localization. To cope with this problem a new objective criterion for iris localization is proposed in this paper based on our visual system. A specific number of points are selected on pupil boundary, iris boundary, upper eyelid and lower eyelid using the original image and then distance from these points to the result of complete iris localization has been calculated. If the determined distance is below a certain threshold then iris localization is considered correct. Experimental results show that proposed criterion is very effective.